PEMBERDAYAAN MASYARAKAT DALAM MENCIPTAKAN LINGKUNGAN YANG BERSIH DAN ASRI MELALUI PENGELOLAAN SAMPAH: Community Empowerment in Creating a Clean and Beautiful Environment through Waste Management - Isnaini Muallidin; Maulida Rita; Angel Purwanti (PUAN INDONESIA, 2023)
This community services were carried out in Banyuurip Padukuhan, Margoagung Village, Seyegan District, Sleman Regency, Special Region of Yogyakarta. After making several observations, problems were found in this area, where the village which is located close to the main road causes environmental problems, especially in terms of environmental cleanliness on the riverbanks. As a result of uncontrolled waste disposal by road users, it has a huge impact on the people of Banyuurip, especially on health, which can cause Dengue Hemorrhagic Fever (DHF) and a less beautiful environment. this community service conducts outreach activities related to waste by sorting household waste and making waste banks. In addition, there is training on making hydroponic plants with the aim that the community can manage waste properly. This community service method goes through several stages, namely the stages of problem identification, planning, implementation of activities, monitoring, and evaluation. the result of community service here is that many people still don't know how to make a waste bank and properly manage hydroponic plants and catfish seeds, so we always carry out monitoring and evaluation related to the constraints felt by the community.